2019
DOI: 10.1371/journal.pone.0213313
|View full text |Cite
|
Sign up to set email alerts
|

Neuroreceptor kinetics in rats repeatedly exposed to quinpirole as a model for OCD

Abstract: Background Obsessive-compulsive disorder (OCD) is a chronic, incapacitating, early onset psychiatric disorder that is characterized by obsessions and compulsions originating from a disturbance in the cortico-striato-thalamico-cortical circuit. We implemented the preclinical quinpirole (QP) rat model for compulsive checking in OCD to analyse the behaviour and visualize the D2R, mGluR5 and GLT1 density in order to contribute to the understanding of the neuroreceptor kinetics. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 42 publications
3
4
0
Order By: Relevance
“…Next to these compulsive checking behaviors, we also characterized hyperactivity measures and specific behavioral acts the rats performed during a visit at the home-base. Quinpirole-injected adolescent rats travelled over a longer total distance and with higher velocity than control rats, corresponding to hyperactivity, which has also been observed in the adult model ( Servaes et al, 2019 ). In addition, in contrast to control animals showing clear grooming behavior during a home-base visit, quinpiroleinjected adolescent rats did not groom, similar to what has been observed in the adult rat model ( Szechtman et al, 1998 ).…”
Section: Compulsive-like Behavioral Phenotypesupporting
confidence: 74%
See 2 more Smart Citations
“…Next to these compulsive checking behaviors, we also characterized hyperactivity measures and specific behavioral acts the rats performed during a visit at the home-base. Quinpirole-injected adolescent rats travelled over a longer total distance and with higher velocity than control rats, corresponding to hyperactivity, which has also been observed in the adult model ( Servaes et al, 2019 ). In addition, in contrast to control animals showing clear grooming behavior during a home-base visit, quinpiroleinjected adolescent rats did not groom, similar to what has been observed in the adult rat model ( Szechtman et al, 1998 ).…”
Section: Compulsive-like Behavioral Phenotypesupporting
confidence: 74%
“…The clear behavioral effects in quinpirole-injected rats may be a direct result of the preceding quinpirole injection, rather than from a change in the macro-scale functional or structural brain connections. Since previous studies have shown abnormalities at the neurotransmitter and receptor level in the quinpirole model ( Servaes et al, 2019( Servaes et al, , 2017, differences in structural and functional connectivity may be more subtle and at the micro-scale. Differences that are not detectable with macro-scale MRI-based measures.…”
Section: Structural and Functional Brain Alterationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Next to these compulsive checking behaviors, we also characterized hyperactivity measures and specific behavioral acts the rats performed during a visit at the home-base. Quinpirole-injected adolescent rats travelled over a longer total distance and with higher velocity than control rats, corresponding to hyperactivity, which has also been observed in the adult model (Servaes et al, 2019). In addition, in contrast to control animals showing clear grooming behavior during a homebase visit, quinpirole-injected adolescent rats did not groom, similar to what has been observed in the adult rat model (Szechtman et al, 1998).…”
Section: Compulsive-like Behavioral Phenotypesupporting
confidence: 74%
“…The development of compulsive-like behavior after repeated quinpirole injections is believed to reflect modifications in the brain due to the sensitization to the dopamine D2receptor agonist quinpirole (Tucci et al, 2014a), such as an increased D2 receptor density (Servaes et al, 2019). The reduced expression of compulsive checking behavior in the adolescent rat model may be explained by maturational differences in dopaminergic receptors in the striatum between day 40 (adolescence) and day 60 (adulthood) (Teicher et al, 1995), potentially resulting in reduced sensitivity to dopaminergic agonists in young rats (Bolanos et al, 1998;Ulloa et al, 2004).…”
Section: Compulsive-like Behavioral Phenotypementioning
confidence: 99%